Bruton's Tyrosine Kinase Mediates the Synergistic Signalling between TLR9 and the B Cell Receptor by Regulating Calcium and Calmodulin - DOYLE, SARAH; O'NEILL, LUKE; QUINN, SUSAN (My University, 2013)
B cells signal through both the B cell receptor (BCR) which binds antigens and Toll-like receptors (TLRs) including TLR9 which recognises CpG DNA. Activation of TLR9 synergises with BCR signalling when the BCR and TLR9 co-localise within an auto-phagosome-like compartment. Here we report that Bruton's tyrosine kinase (BTK) is required for synergistic IL6 production and up-regulation of surface expression of MHC-class-II, CD69 and CD86 in primary murine and human B cells. We show that BTK is essential for co-localisation of the BCR and TLR9 within a potential auto-phagosome-like compartment in the Namalwa human B cell line. Downstream of BTK we find that calcium acting via calmodulin is required for this process. These data provide new insights into the role of BTK, an important target for autoimmune diseases, in B cell activation.
PUBLISHED
Keywords: B Cell receptors; Immunology, Inflammation & Infection; Biomedical sciences; Intra and intercellular signalling